2008
DOI: 10.1145/1352582.1352588
|View full text |Cite
|
Sign up to set email alerts
|

What causes a system to satisfy a specification?

Abstract: Even when a system is proven to be correct with respect to a specification, there is still a question of how complete the specification is, and whether it really covers all the behaviors of the system. Coverage metrics attempt to check which parts of a system are actually relevant for the verification process to succeed. Recent work on coverage in model checking suggests several coverage metrics and algorithms for finding parts of the system that are not covered by the specification. The work has already prove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
65
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 37 publications
(66 reference statements)
0
65
0
Order By: Relevance
“…However, each of the marksmen has degree of blame 1/10. The complexity of determining the degree of responsibility and blame using the original definition of causality was completely characterized (Chockler & Halpern, 2004;Chockler, Halpern, & Kupferman, 2008). Again, we show that changing the definition of causality affects the complexity, and completely characterize the complexity of determining the degree of responsibility and blame with the updated definition.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…However, each of the marksmen has degree of blame 1/10. The complexity of determining the degree of responsibility and blame using the original definition of causality was completely characterized (Chockler & Halpern, 2004;Chockler, Halpern, & Kupferman, 2008). Again, we show that changing the definition of causality affects the complexity, and completely characterize the complexity of determining the degree of responsibility and blame with the updated definition.…”
Section: Introductionmentioning
confidence: 76%
“…In the original HP model, it was shown that computing responsibility is FP NP[log n] -complete in binary causal models (Chockler et al, 2008) and FP Σ P 2 [log n] -complete in general causal models (Chockler & Halpern, 2004). First, we prove that the FP Σ P 2 [log n] -completeness result holds for singleton causes.…”
Section: Responsibilitymentioning
confidence: 93%
“…We obtain tractability by restricting our queries to conjunctive queries. Chockler et al [6] have shown that causality for "read once" Boolean circuits is in PTIME. Our results are strictly stronger: for the case of conjunctive queries without self-joins, queries with read-once lineage expressions are precisely the hierarchical queries [8,20], while our results apply to all conjunctive queries.…”
Section: Complexity Of Causalitymentioning
confidence: 99%
“…In order to achieve an efficiently computable approximation, our algorithm is inspired by the algorithm for read-once formulas in [3]. It involves one traversal of the circuit for each l ∈ I X (r) and its overall complexity is only quadratic in the size of M .…”
Section: Computing Degree Of Responsibility In Treesmentioning
confidence: 99%
“…Inspired by the algorithm for read-once formulas in [3], we developed the algorithm RespST E for efficiently computing an approximate DoR. Computing the responsibility of the inputs for some output of a circuit involves one traversal of the circuit for each X valued input in the cone of influence of the output.…”
Section: Introductionmentioning
confidence: 99%